Guidelines for regulating the principle of subsidiarity in the mortgage credit market - Félix Acosta, Nataly (2025)
This article analyzes the application of the principle of subsidiarity in mortgage loans granted by the Banco de la Nación, highlighting the differing approaches of the Constitutional Court and Indecopi. The former emphasizes social need, while the latter prioritizes market competition and the adequacy of private supply, considering state intervention justified only when the private sector fails to meet demand effectively.In light of the lack of consistent criteria, we propose guidelines to assess subsidiarity in the granting of these loans and to prevent market distortions. Additionally, we present alternatives to ensure the continued operation of the Banco de la Nación, guaranteeing that its involvement respects the principle of subsidiarity and remains complementary to private banking.